1991
DOI: 10.1007/bf02347132
|View full text |Cite
|
Sign up to set email alerts
|

Downhill movement of litter and its implication for ecological studies in three types of forest in Japan

Abstract: The amount of litter moving down the slope was measured in three types of forest, together with an examination of rain as a factor in bringing this about. The three forest types were a natural mixed stand of Pinus densiflora and hardwood trees (plot A), a Cryptomeria japonica plantation (plot S) and a Chamaecyparis obtusa plantation (plot H). The amount of moved litter was quite large in plots A and H, but relatively small in plot S. The rain factor had little influence on litter movement in plot A, but was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 1 publication
1
33
0
Order By: Relevance
“…Red pine litter consists of slender needles, which are not easily moved (Hattori et al 1992). Sugi litter also does not move easily, because it remains attached to branches on the forest floor for a long time (Tsukamoto 1991). These differing properties of the leaf litter result in different floor litter conditions, and consequently a wide range of FCPs, from 50% to 100% (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Red pine litter consists of slender needles, which are not easily moved (Hattori et al 1992). Sugi litter also does not move easily, because it remains attached to branches on the forest floor for a long time (Tsukamoto 1991). These differing properties of the leaf litter result in different floor litter conditions, and consequently a wide range of FCPs, from 50% to 100% (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The significance of cover near the ground for erosion processes on slopes has previously been pointed out in artificial rainfall experiments (Mihara 1951; Kawaguchi and Takiguchi 1957;Murai and Iwasaki 1975). Tsukamoto (1991) found that rain factor had strong influence on Japanese cedar and especially cypress litter movement. Miura et al (2003) reported the importance of forest cover conditions on young cedar plantations; Tsukamoto (1991) pointed out that, in the case of cedar species, litter does not move easily because it remains attached to branches on the forest floor for a long time.…”
Section: Introductionmentioning
confidence: 98%
“…Tsukamoto (1991) found that rain factor had strong influence on Japanese cedar and especially cypress litter movement. Miura et al (2003) reported the importance of forest cover conditions on young cedar plantations; Tsukamoto (1991) pointed out that, in the case of cedar species, litter does not move easily because it remains attached to branches on the forest floor for a long time. Also, previous studies showed that more mass mortality of trees especially due to xylem degradation seem to increase in the future in unmanaged conifer forests (Kuroda 2003); however, Sato (2007) reported that thinning prevents insect and disease outbreaks.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Under wet conditions (14 samples, M6Ј was the result that the slope inclination was 28°), the erosion rates at points M6, M10, M13, and M14 were large (0.4-0.6 mm). These samples were all composed of decomposed litter, which is easily eroded by rain splash (Tsukamoto 1991). Other samples composed of fresh litter were hardly eroded at all.…”
Section: Rain Splash Erosion Rates Of Each Horizonmentioning
confidence: 99%